A prominent role for mucosal cystine/cysteine metabolism in intestinal immunoregulation - Sido, Bernd; Lasitschka, Felix; Giese, Thomas; Gaßler, Nikolaus; Funke, Benjamin; Schröder-Braunstein, Jutta; Brunnemer, Ulf; Meuer, Stefan; Autschbach, Frank (Gastroenterology, 2008)
BACKGROUND & AIMS: T-cell receptor reactivity of intestinal lamina propria T cells (LP-T) critically depends on the capacity of local accessory cells to secrete cysteine. For T cells, cysteine is the limiting precursor for glutathione synthesis, a prerequisite for antigen-dependent proliferation. We aimed to determine the role of the redoxactive microenvironment for hyporeactivity of LP-T in normal human gut vs hyperreactivity of LP-T in inflammatory bowel disease. METHODS: Parameters relevant to cysteine production, determined as acid-soluble thiol, by intestinal lamina propria macrophages (LP-MO) vs peripheral blood monocytes were investigated (L-[(35)S]cystine uptake via system x(c)(-), messenger RNA, and protein expression of the cystine transporter subunit xCT). Glutathione levels in LP-T and peripheral blood T cells were analyzed both spectrophotometrically and by immunofluorescent staining in situ and in vitro. RESULTS: LP-MO from normal gut, unlike peripheral blood monocytes, are unable to take up cystine, which is due to a deficient expression of the transporter xCT in situ and in vitro. As a consequence, LP-MO do not secrete cysteine. The glutathione content in LP-T from normal gut is <50% of that in autologous peripheral blood T cells. In contrast, in inflammatory bowel disease, CD14(+)CD68(+) LP-MO express xCT and secrete substantial amounts of cysteine upon stimulation, which results in high glutathione levels and full T-cell receptor reactivity in LP-T. CONCLUSIONS: The antioxidative microenvironment of LP-T in inflammatory bowel disease and the prooxidative microenvironment in normal gut explain the differential T-cell receptor reactivities.